Pilgrimage, Cartography, and Devotion: William Wey's Map of the Holy Land - Arad, Pnina (Viator, 2012)
Abstract This article offers a reconstruction of a chapel, set up in England in the 1470s to commemorate a pilgrimage to the Holy Land. The reconstruction follows information drawn from the founder‘s will. Made up of architectural components, paintings, wooden models, stones, maps, and a manuscript narrative, the composition was designed to evoke the Holy Land in England. Rooted as it is in the tradition of architectural response to pilgrimage, it also appears to be a product of a different tradition and use of architecture, that of the English Easter Sepulchre. A map of the Holy Land preserved in the Bodleian Library seems to be the only component to have survived. The article studies the installation in relation to a wide-ranging European tradition, that of relocating the Holy Land in the homeland, and discusses in more detail the insertion of a map of the Holy Land into the category of fifteenth-century devotional imagery.